Preferência alimentar e eficiência da carpa capim (Ctenopharyngodon idella) no controle de macrófitas aquáticas em mesocosmos - Silva, Adilson Ferreira da [UNESP] (2014)
The macrophytes may be problems in many water bodies, being necessary to employ control technique. The use of grass carp fish (Ctenopharyngodon idella) is an established biological control technique in many countries. The aim of this study was to evaluate the efficiency of food preference and control of diploid grass carp exposed the macrophytes Ceratophyllum demersum, Egeria densa, Egeria najas and Hydrilla verticillata isolated and combined condition micro and mesocosms. To this, three experiments were conducted. The first experiment was the supply and planting of macrophytes C. demersum, E. densa and E. najas in microcosms of 250 liters with five repetitions in completely randomized design (CRD). In the second and third experiment plants were offered in isolated and combinated condition mesocosms 2000 L. In the second experiment the plant C. demersum, E. densa and E. najas was used, in the third experiment the macrophyte C. demersum, E. densa, E, najas and H. verticillata in a randomized block design (RBD) in triplicate. In the first experiment the treatment with lower quantity of fish were what to show the bigger consumption and to get in weight in conditions of microcosms. In the second experiment the plant more predated by grass carp was E. najas and C. demersum when offered alone, and when offered together the order of food preference was C. demersum > E. najas > E. densa. In the third experiment the plant most consumed either alone or in combination was the H. verticillata and the least consumed was E. densa. Thus, it is concluded that use of grass carp (C. idella) as a biological control agent has advantages for having high rates of consumption and in greater preference for H. verticillata, followed by E. najas and C. demersum and lower intensity in the E. densa in mesocosms condition, which makes the grass carp one great tool for biological control